Análise discursiva das novas diretrizes curriculares nacionais para as licenciaturas - Santos, Cristiane Silva (2018)
The social, political and economic transformations that Brazil has undergone in the last years and obviously with repercussions in all areas of society are great. In school education, the training field of individuals, these changes are "proposed" through legislation that regulates teaching and presents a discourse to meet new social demands. In the whole legislation on teacher education in Basic Education, the New National Curriculum Guidelines for Undergraduate Courses for Teachers were approved and homologated in 2015. This document proposes a policy of formation and valorization of teaching in a political and economic context that contradicts the legislation itself and, therefore, a discursive analysis of the document and the senses produced from its publication is pertinent. Thus, this research has as main objective to unveil the senses present in the functioning of the teacher training discourse in the DCN using the theoretical instrumentation of the French AD. We use as a theoretical contribution Pêcheux (1990, 2010, 2014, 2015), which bases the theory of non-subjective reading and supports discourse as a historical materiality accessed through texts; Althusser (1998); Orlandi (2000, 2014, 2015); Foucault (2007), as well as studies that involve the field of education, aimed at teacher education and the bases that support the educational legislation in force, arranged by Libâneo (2010, 2012) and other authors, whose critics contribute to the elaboration of the our work. We select as an object of analysis the discourse about teacher education, present in the New National Curricular Guidelines. In order to meet the objective of our research, we use the qualitative research methodology whose objective is to understand the functioning of the discourses in the object already mentioned. In order to meet the objective of our research, we selected as corpus the discursive sequences contained in CNE / CP Resolution 2 of July 1, 2015 and elaborated the following questions to guide our analysis, namely: a) How the proposal is presented teacher training in the new guidelines? b) In what context were these DCN been / are being presented? c) What are the subject positions occupied by the interlocutors? d) What discursive / ideological formations are involved in these proposals? e) What effects of meaning present in the proposals / policies of the current teacher conception? We have seen the resumption of "already said" in proposals that are presented as a solution to meet the new social demands of the teaching profession and that are related to other discourses strongly influenced by the conception of the neoliberal politics of capital, manifested by the discursive formation of the market occupied by the position -subject that holds the power to institute the norms of teaching and discipline the individuals.